Principles of electrodynamics - Schwartz, Melvin, 1932-2006 (International series in pure and applied physics., 1987)
This advanced undergraduate- and graduate-level text by the 1988 Nobel Prize winner establishes the subject's mathematical background, reviews the principles of electrostatics, then introduces Einstein's special theory of relativity and applies it throughout the book in topics ranging from Gauss' theorem and Coulomb's law to electric and magnetic susceptibility.